Subsistence fishing methods of Manguisog Mercedes, Camarines Norte - Estacio, Felix S. (College of Fisheries, University of the Philippines, 1953)
Fishing is one of the basic industries of the Philippines. Since there are about 2,000 species of fish in the Philippines waters, some of which are highly important as export, it is paramount that we improve this industry. The Philippines is now inhabited by a greater number of people as compared before the war, whose basic food is rice and fish. Since the Philippines is rich in fishery resources and its inhabitants are fish-eating people, the fish supply must be plentiful. However, fish is generally expensive and the supply cannot meet the demand. An abundant supply of fish occur only a few times and only at fishing villages. This condition is due partly to lack of modern fishing vessels and modern fishing gears. Modern fish capture must be made known as capitalist for its possibility as moneymaking industry. The fish capture section of the Philippine institute of fisheries technology is making progress in their effort to improve our local method of capturing fish and introducing modern methods of fishing gears from other countries. To help the industry, students are being trained and sent to the field equipped with two years of theoretical and practical training plus six months of actual experience. My three months practical training in Maguisoc, Mercedes, Camarines Norte with Mr. Tomas Delos Reyes, gave the knowledge in the actual operation of the "basing". The rest of my practical training in industry was in the Northern part of Laguna de Bay gathering some datas regarding the progress of Fish corrals and its cath.